Analisis Preferensi Konsumen Terhadap Minat Beli Buah Mangga Arum Manis di Pasar Tradisional Kota Semarang - Pratama, Erick Tahta; Ekowati , Titik; Santoso , Siswanto Imam (Badan Riset dan Inovasi Daerah Provinsi Jawa Tengah, 2024)
This research aims to analyze the characteristics of consumers, the influence of the number of family members on the purchase of Arum Manis mango, and to analyze the attributes and preferences of consumers towards Arum Manis mango in traditional markets in Semarang City. The research was conducted in four traditional markets in Semarang City, namely Johar Market, Peterongan Market, Bulu Market, and Karangayu Market. The research method used was a survey method using a questionnaire and non-probability sampling with quota sampling technique of 50 respondents. The analysis methods used were descriptive analysis, crosstab analysis, and chi-square analysis to determine the influence of the number of family members on the purchase of Arum Manis mango, and conjoint analysis to determine the attributes of Arum Manis mango that can affect consumer preferences for mangoes in traditional markets in Semarang City. The results showed that consumers of Arum Manis mango in traditional markets in Semarang City have characteristics including: on average, consumers are 41 years old, the majority of buyers are female, the majority of consumers have a diploma III/IV/Bachelor's degree, consumers with the highest number of family members are 4 people, and the majority of consumers have an income of Rp. 2,500,000.00. The results of the chi-square and crosstab analysis showed the influence of the number of family members on the purchase of Arum Manis mango. The conjoint analysis results showed that consumers prefer Arum Manis mangoes that are light green or yellowish in color, sweet in taste, and small in size. The order of the most important attributes of Arum Manis mango for consumers during the purchase process based on the Importance Values is the size attribute with a percentage of 39.26%, followed by taste with 33.87%, and color with 26.87%.